2006
DOI: 10.2140/pjm.2006.226.1
|View full text |Cite
|
Sign up to set email alerts
|

Homology multipliers and the relation type of parameter ideals

Abstract: The relation type question, raised by C. Huneke, asks whether for a complete equidimensional local ring R there exists a uniform number N such that the relation type of every ideal I ⊂ R generated by a system of parameters is at most N. Wang gave a positive answer to this question when the non-Cohen-Macaulay locus of R (denoted by NCM(R)) has dimension zero. In this paper, we first present an example, due to the first author, which gives a negative answer to the question when dim NCM(R) ≥ 2. The major part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Wang [19] showed that two-dimensional local rings always have this property. Recently, Aberbach, Ghezzi and Ha [1] found out that certain local rings with one-dimensional non-Cohen-Macaulay locus also have this property. Therefore, the class of local rings with this property must be larger than the class of generalized Cohen-Macaulay rings.…”
Section: Remark For Any M-primary Ideal I Of a Generalized Cohen-macmentioning
confidence: 95%
See 2 more Smart Citations
“…Wang [19] showed that two-dimensional local rings always have this property. Recently, Aberbach, Ghezzi and Ha [1] found out that certain local rings with one-dimensional non-Cohen-Macaulay locus also have this property. Therefore, the class of local rings with this property must be larger than the class of generalized Cohen-Macaulay rings.…”
Section: Remark For Any M-primary Ideal I Of a Generalized Cohen-macmentioning
confidence: 95%
“…This problem originated from Huneke's question whether equidimensional unmixed local rings have the above property. Recently, Aberbach found a counter-example (see [1]). Results of Wang [19] and of Aberbach, Ghezzi and Ha [1] showed that the class of rings with the above property must be larger than the class of generalized Cohen-Macaulay rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, consider the ideals generated by a system of parameters. C. Huneke asked in [16] whether there is a uniform bound for the relation type of these ideals in a complete local equidimensional Noetherian ring R. The full answer to this question was given in [28], [19] and [1]. Concretely, in [1, Example 2.1], it was shown that if the non-Cohen-Macaulay locus of R has dimension 2 or more, there exist families of parametric ideals of R with unbounded relation type.…”
Section: In Particular If J Is a Reduction Of I With Reduction Numbementioning
confidence: 99%
“…, d − 1. Then there exist an integer s ≥ 1 such that, for every ideal I of A generated by a system of parameters, the relation type of I is bounded above by s.For rings of dimension 3 or more, see the very recent work of Aberbach, Ghezzi and Ha[1].…”
mentioning
confidence: 99%